The impact of cardiac rehabilitation on the tolerance of physical exercise in patients after myocardial infarction - Kałużna, Anna; Wojtulska, Dorota; Kitschke, Ewa; Kałużny, Krystian; Żukow, Walery (Journal of Education, Health and Sport, 2018)
The aim of this study was evaluation of the impact of complex cardiac rehabilitation on the improvement of exercise tolerance of patients after myocardial infarction. Material and methods: Sixty patients after myocardial infarction underwent cardiac rehabilitation (physical activities, cardio-respiratory exercise, education). Their heart rate, blood pressure, energy expenditure and duration of exercise tolerance test were evaluated. Results: Resting heart rate was slightly reduced and exercise heart rate increased as a result of cardiac rehabilitation. Blood pressure did not change significantly after rehabilitation. Energy expenditure was changed from 5.74 MET before rehabilitation to 7.56 MET after it. Duration of exercise tolerance test was changed from 5.07 min. To 7.34 min. Conclusion: Myocardial infarction causes significant reduction of exercise tolerance of the patient. After cardiac rehabilitation resting heart rate does not change and exercise heart rate increases as well as energy expenditure and duration of exercise tolerance test. As a result of cardiac rehabilitation exercise tolerance of patients after myocardial infarction increase.